4. LOYALTY OF ISLAMIC BANKING CUSTOMERS: BANK MANAGERS’ PERSPECTIVES - Abdul Hadi, Noradilah; Muwazir, Mohd Rizal; Kamarudin, Nur Shuhada (Journal of Islamic, Social, Economics and Development, 2024)
The purpose of this paper is to explore bank managers’ perspective on loyalty behaviour of Malay, Chinese and Indian customers in Malaysian Islamic banking industry. This study utilises qualitative approach through the use of semi-structured interview to gain insights of bank managers concerning loyalty behaviour of their multi-ethnic customers. It can be concluded that Islamic banking customers are not loyal to their banks, according to majority of participants. In addition, there were mixed reviews on the influence of ethnicity towards loyalty behaviour of customers. Some interviewees acknowledged loyalty among Malay customers while Chinese customers were more concerned on pricing. Furthermore, there are various reasons why customers choose to be loyal to their banks. First reason is excellent service quality, followed by past experiences of the customers with the banks. One of the interview participants remarked that loyalty can be built by cross selling to the customers as an effort from bank to ensure customers stay with them. This study is conducted to gain insights from Islamic banks’ managers towards loyalty behaviour of their multi-ethnic customers. The findings are significant considering cultural differences might affect the decision making of these customers and ethnicity has a major impact on Malaysian society. The incorporation of culture in the marketing strategies of Islamic banks in Malaysia could strengthen the relationship between banks and their customers.